Slovenia: Challenges of Sovereignty, Lukewarm Implementation of EU Taxation Rules - Bohinc, Rado; Jovanovič, Dušan (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter provides an in-depth exploration of the intricate relationship between tax policy, national sovereignty, and competition in Slovenia, with a specific focus on relevant case law and court decisions. As an European Union (EU) Member State, Slovenia grapples with the dual challenges of harmonising its tax policies with EU directives and preserving its national sovereignty and economic competitiveness. Similar to other EU members, Slovenia is deeply influenced by supranational tax regulations that aim to create a unified market and prevent harmful tax practices. These regulations have led to significant national legal developments, with court decisions related to the interpretation and implementation of EU tax directives shaping the country’s tax policy landscape. For instance, the Court of Justice of the European Union (CJEU) has rendered judgments that impact Slovenia’s approach to tax policy, making it necessary for the country to navigate EU legal interpretations while preserving its national sovereignty. Furthermore, domestic courts in Slovenia have played a crucial role in shaping tax policy through their interpretation of national tax laws and alignment with EU principles. Case law on issues such as transfer pricing, cross-border taxation, and tax evasion has significantly influenced the way Slovenia frames its tax regulations. Court decisions often play a pivotal role in defining the extent to which national sovereignty can be preserved while adhering to EU directives. Simultaneously, the Slovenian government acknowledged the importance of tax competitiveness in attracting foreign investment and promoting domestic entrepreneurship. This chapter examines the multifaceted nature of tax policy in Slovenia by considering the roles of case law and court decisions in shaping the landscape. By examining relevant case law, this study aims to provide a comprehensive analysis of the legal dynamics that underpin Slovenia’s tax policy, offering insights into the country’s economic future and ability to navigate the challenges of EU membership. Keywords: tax sovereignty, tax competition, tax harmonisation, property taxes, income taxes, global minimum tax, corporate income tax